Pengembangan UMKM: Digitalisasi Pemasaran, Pembayaran, dan Layanan Pesan Antar - Rokhmad Thoriqul Hidayat; Jahroni Jahroni; Utami Puji Lestari (Joong-Ki : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen the competitiveness of the Tahu Tek Pak Lajim MSME through modernizing business management, including implementing digital marketing strategies, integrating a QRIS-based electronic payment system, and optimizing the use of online food ordering platforms. The method used is Asset-Based Community Development (ABCD) with five stages: discovery, dreaming, design, defining, and destiny, which are implemented over a month. The discovery stage is carried out through observation and interviews to identify the business's internal assets, including product advantages, customer base, and initial marketing and transaction conditions. The dreaming stage focuses on formulating a vision for digital-based business development with partners. The design stage is directed at planning training and developing strategies for digitalizing marketing, payments, and delivery services. The defining stage is carried out through intensive mentoring and direct practice using social media, Google Maps, QRIS, and online food ordering using the GoFood. The destiny stage is carried out through initial monitoring and evaluation of program sustainability. The results of the community service program demonstrate increased business visibility through the use of social media and Google Maps, ease of transactions through the implementation of QRIS-based cashless payments, and expanded consumer reach through the integration of online delivery services using the GoFood. This digitalization contributes to increased operational efficiency and sales stability for MSMEs